A New PqsR Inverse Agonist Potentiates Tobramycin Efficacy to Eradicate Pseudomonas aeruginosa Biofilms. Issue 12 (18th March 2021) - Schütz, Christian; Ho, Duy‐Khiet; Hamed, Mostafa Mohamed; Abdelsamie, Ahmed Saad; Röhrig, Teresa; Herr, Christian; Kany, Andreas Martin; Rox, Katharina; Schmelz, Stefan; Siebenbürger, Lorenz; Wirth, Marius; Börger, Carsten; et al.
Abstract: Pseudomonas aeruginosa (PA) infections can be notoriously difficult to treat and are often accompanied by the development of antimicrobial resistance (AMR). Quorum sensing inhibitors (QSI) acting on PqsR (MvfR) – a crucial transcriptional regulator serving major functions in PA virulence – can enhance antibiotic efficacy and eventually prevent the AMR. An integrated drug discovery campaign including design, medicinal chemistry‐driven hit‐to‐lead optimization and in‐depth biological profiling of a new QSI generation is reported. The QSI possess excellent activity in inhibiting pyocyanin production and PqsR reporter‐gene with IC50 values as low as 200 and 11 × 10 −9 m, respectively. Drug metabolism and pharmacokinetics (DMPK) as well as safety pharmacology studies especially highlight the promising translational properties of the lead QSI for pulmonary applications. Moreover, target engagement of the lead QSI is shown in a PA mucoid lung infection mouse model. Beyond that, a significant synergistic effect of a QSI‐tobramycin (Tob) combination against PA biofilms using a tailor‐made squalene‐derived nanoparticle (NP) formulation, which enhance the minimum biofilm eradicating concentration (MBEC) of Tob more than 32‐fold is demonstrated. The novel lead QSI and the accompanying NP formulation highlight the potential of adjunctive pathoblocker‐mediated therapy against PA infections opening up avenues for preclinical development. Abstract : The discovery and profiling of a novel Pseudomonas aeruginosa ‐targeting Quorum Sensing Inhibitor (QSI) with high anti‐virulence efficacy, favorable DMPK and no overt safety pharmacology is reported. The in vivo target engagement of the lead QSI in a mucoid lung‐infection mouse model is demonstrated. Importantly, the application of a state‐of‐the‐art squalene‐based nanocarrier formulation boosts tobramycin susceptibility of biofilms.